ANALYSIS OF “PEER FRIENDS” VLOG ON THE LEARNING MOTIVATION OF MAHARAH ISTIMA’ UIN MALANG STUDENTS - Habibah, Ihda Filzafatin; Fitriani, Laily; Aziz, Abdul (Proceeding of International Conference on Islamic Education (ICIED); Vol 8 No 1 (2023): Proceeding of International Conference on Islamic Education (ICIED), 2024)
This study aims to determine the results of "peer" vlog analysis on the learning motivation of Maharah Istima' a new student of Arabic Language Education at UIN Maulana Malik Ibrahim Malang. This is based on the main problem of students in digesting Arabic as a language that is difficult to learn, especially in maharah istima' which has a stereotype of "boring" because it only focuses on one thing, namely listening and digesting speech or guidance by others, even though maharah istima' itself is the most basic thing that must be understood and mastered before stepping on other language skills. The research method supported by some theories and that support this domain by supporting documents and based on survey. This research is a new thing that appears in the world of Arabic language learning, especially Maharah Istima' which has been containing difficult labeling even by Arabic students themselves. In the results of this study, it was found that the basic thing that makes new students of the Arabic study program motivated in learning maharah istima' is because of external factors, namely "peer vlogs". Of course, this attracts attention, especially it can be a reference for one of the models or methods of learning maharah istima' in various ways that exist.